Association between ethylene oxide exposure and Klotho levels in US adults - Huanli Zhang; Zhen Zhang (Scientific Reports)
Abstract Ethylene oxide (EO) is an industrial chemical used in the production of both consumer and non-consumer products.Additionally, it is utilized as a gaseous sterilant for medical devices. As an anti-aging hormone, kloth involved in various physiological processes. At present, the association between EO exposure and klotho remains uncertain. In this retrospective cross-sectional study, 1696 participants aged 40–79 years in the 2013–2016 National Health and Nutrition Examination Survey were included. EO exposure was measured using the hemoglobin adducts of EO (HbEO) in human whole blood or erythrocytes. Klotho levels were also measured in blood samples. Linear regression, smooth curve fitting, and subgroup analyses were used to assess whether HbEO was associated with klotho level. After full adjustment for confounders, the negative association between log2HbEO and klotho was observed after multivariate adjustment (β=−17.29, 95% CI = − 28.42 ~ − 6.17, P = 0.002). When EO was categorized into quintiles, the fifth quintile exhibited significant differences compared to the lowest quintile (β=−70.79, 95% CI = − 122.54 ~ − 19.04, P = 0.007). The curve fitting shows an inverse “L-shaped” relationship between log2HbEO and klotho (P for nonlinearity = 0.04). In summary, a negative and nonlinear relationship was found between log2HbEO and klotho. Further research is required to confirm the causality of this connection and clarify the underlying mechanisms.